PENGARUH PERATURAN MENTERI KESEHATAN (PERMENKES) NO. 3 TAHUN 2023 TERHADAP PERSEDIAAN DI KLINIK HEMODIALISA - Yusriyadi Firdha Alphionita (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Hemodialysis clinic is one place that provides services and facility hemodialysis for out patient. As a clinic, it should obey for minister of health regulation in Indonesia because a hemodialysis clinic has collaborated with BPJS as health insurannce agency. Changes in inventory due to the latest provisions are one of the clinic’s efforts to provide better services. Changes in the use of supplies will be able to change the quantity of purchases of medical equipment and materials. For clinics, supplies are an important element in the operation of hemodialysis services. Clinics that have systematic inventory records will always maintain inventory records so that they can know the amount of supplies used in clinic operations. The purpose of this paper is to analyze changes in supplies caused by the health minister's regulations. Changes in inventory can be seen through the amount of inventory purchased and the amount of inventory used. Because changes in inventory also affect the gross profit of the Hemodialysis Clinic. The results of the research show that the quantity of supplies purchased has increased, the amount of inventory used has increased, and the clinic's gross profit has decreased.